Analysis of stress transfer in short fiber-reinforced composites with a partial damage interface by a shear-lag model. (September 2021) - Hu, Yan-Gao; Ma, Y.L.; Hu, C.P.; Lu, X.Y.; Gu, S.T.
Abstract: The stress transfer mechanism in fiber-reinforced composites with a partial damage interface was investigated by a newly developed shear-lag model with a cohesive interface. The analytical solutions of the interfacial shear stress and the normal stress in the fiber at a damage stage were obtained. Analytical expressions of the critical stress corresponding to the initiation of damage or debonding of the interface were derived. The analytical solutions agreed well with the numerical results and existing experimental results. Highlights: The analytical solutions of the interfacial stress at a damage stage were obtained. Analytical expressions of the critical stress for the interface debonding were derived. The analytical solutions agreed well with the numerical results and existing experimental results.